Hybrid Meetings in the Modern Workplace: Stories of Success and Failure - Saatci, Banu; Rädle, Roman; Rintel, Sean; O'Hara, Kenton; Klokmose, Clemens Nylandsted (CollabTech 2019, 2019)
Hybrid meetings, in which co-located and remote participants connect via video or/audio, have become ubiquitous in the globalized modern workplace. Despite, or perhaps because of this ubiquity, conducting hybrid meetings is not straightforward. In this paper, we investigate the opportunities and challenges of hybrid meetings. We conducted a multi-site study of hybrid meetings in two global software companies in Europe, using participant observation, semi-structured interviews and video-analysis. Our findings show that there is a significant diversity in formats and requirements for hybrid meetings in different working environments. Further, hybrid meeting participants perceive and handle a range of both expected and emergent problems. While some problems can be attributed to difficulties or failures of technical infrastructure, others arise out of asymmetries of interaction and social and cultural context across the co-located and remote settings. We argue that managing these asymmetries is key to a successful hybrid meeting.
Cite as: Saatçi B., Rädle R., Rintel S., O’Hara K., Nylandsted Klokmose C. (2019) Hybrid Meetings in the Modern Workplace: Stories of Success and Failure. In: Nakanishi H., Egi H., Chounta IA., Takada H., Ichimura S., Hoppe U. (eds) Collaboration Technologies and Social Computing. CRIWG+CollabTech 2019. Lecture Notes in Computer Science, vol 11677. Springer, Cham https://doi.org/10.1007/978-3-030-28011-6_4